(untitled) (Research, Society and Development, 2021)
Introduction: Knowledge of the anatomy and root canal system is of fundamental importance for a successful endodontic treatment. Maxillary canines unusually possess two root canals. Aim: The present study aims to present a maxillary canine with two roots and two canals through a clinical case. Case report: A male patient was referred for the treatment of a root perforation of the tooth 23. Clinical examination revealed the presence of vestibular fistula and mild pain with vertical and horizontal percussion. Through a tomographic examination, the presence of two roots and two root canals was observed in addition to a radiolucent lesion at the middle third of the roots but without perforation in the middle third. Coronary opening and the localization of the vestibular and palatal canals were performed. The root canal length was performed with Romi Apex A-15® foraminal locator and instrumentation was conducted by using Protaper Next® system. Due to the presence of fistula, calcium hydroxide manipulated with propylene glycol was used as intracanal medication for 30 days. After this period, the root canals were filled with gutta-percha and AH Plus® cement and a new tomographic examination was undertaken, which confirmed the complete filling of the root canals and the absence of root perforation. Conclusion: Given the above, endodontic professionals shall be aware of possible anatomical variations and make use of auxiliary resources when appropriate, such as cone beam computed tomography (CBCT), to ensure correct diagnosis and, consequently, a successful root canal treatment.